Chapter La bellezza come strumento di accesso alla conoscenza storica. La mostra Scuole come capanne. Libri come opere d'arte. Dal Brasile all'Agro romano - Vagliani, Pompeo (Studi e saggi, 2019)
The essay deals with the exhibition "Schools as huts and books as works of art. From Brazil to the Agro Romano" (Scuole come capanne e libri come opere d'arte. Dal Brasile all'Agro Romano), which collected educational materials and objects of daily life made for the schools of the Brazilian Indians, as well as those of the farmers of the Agro Romano of the early 20th Century. The dialogue between these materials underlines the centrality of beauty in education and in creating a better world.